Sosialisasi Fasilitas Kredit Usaha Mikro Dan Kredit Usaha Rakyat di Arso XIV Kabupaten Keerom - Elsyan Rienette Marlisa; Andarias Kuddy (The Community Engagement Journal, 2020)
The Purpose of community devotion is 1) to know and understand the banking products. 2) to know and understand the credit facilities of MICRO Enterprises (KUM) and credit People's Business (KUR) PT. Bank Mandiri (Persero) TBK. Based on the results of the community service made to the community of dragon fruit farmers in Arso XIV Keerom District can be concluded the following things: 1). The banking office can be understood through the submission of the lecturer who is devoted to the community and the speaker of the employee Micro Banking Manager PT. Bank Mandiri (Persero). Tbk. Introduction of the lecturer on the purpose and objectives. Explaining the meaning of the Bank is a business entity that raises funds from the community in the form of deposits and reorganized funds that have been compiled through Giro deposits, savings and deposits to the community in the form of loans (loanable Fund) for conventional banks. For conventional banks can provide interest-charged loans and other lending services in the form of administrative fees, provision fees, and commissions. In The material delivery to the people of the dragon fruit farmers in ARSO XIV Keerom District in this case the mothers in ARSO XIV of Keerom District are very motivated in understanding and can distinguish Micro Business credit (KUM) and the People's Business Credit (KUR) FROM PT. Bank Mandiri (Persero) TBK, so that it can develop a community business through the facilities of the People's Business Credit (KUR) from PT. Bank Mandiri (Persero) TBK